Pengembangan Butir Soal Tes Kinerja pada Mata Pelajaran Kimia SMA Berdasarkan Keterampilan Proses Sains - Muhammad Merlis; Effendi Effendi; Hartono Hartono (Seminar Nasional Pendidikan IPA Tahun 2021, 2021)
This research aims to develop an assessment rubric items and performance tests based on the basic science process skills. This type of research is research and development (development research). The model used to follow the model of the development of a test that consists of stages Defining the test universe, audience, and purpose; Developing a test; Revising the test; and Validation the test. The resulting product tested by a teacher and students of class XI MIA Senior Hight School of Srijaya Negara in Palembang. The results stating that the products are practice with percent average of practicality is reached 76%, and meet the criteria forreliable with a Cronbach alpha value is 0.727. Validator declared product that developed is valid and fit for use. Obtained empirical validity of the value ofthe test results indicate that the products included in the categoryis valid.